Kinerja Karyawan Marketing Bank BRI Syariah di Malang - Puspitasari, Della; Rachmawati, Lucky (Jurnal Ekonomika dan Bisnis Islam, 2019)
This research was conducted at BRI Bank Syariah in Malang, the purpose of the study was to determine the effect of incentive, leadership style, age, education, gender and the lenght of work on the performance of marketing employees. This analysis used is multiple regression analysis. The results of multiple regression tests are : the amount of incentives has a significant effect on employee performance. Leadership style has a significant effect on employee performance. The age of employees does not have a significant effect on employee performance. Gender employees have ni significant effect on employee performance. The duration of work of employees influences employe performance. There is influence together (simultaneous). Together the magnitude of incentives, leadership style, age, education, gender, and lenght of work affect the performance of marketing employees.